2012
DOI: 10.1089/acm.2012.1502
|View full text |Cite
|
Sign up to set email alerts
|

Biofield Research: A Roundtable Discussion of Scientific and Methodological Issues

Abstract: Richard Hammerschlag: This discussion will be among the participants of a symposium on clinical and basic science research on the biofield, held as part of the International Research Congress on Integrative Medicine and Health in Portland, Oregon in May 2012. The 7 of us are conventional biomedical researchers in physiology, clinical psychology, cell biology, biophysics, and neurobiology, who through various paths have expanded our research interests to include performing preclinical studies, clinical trials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 37 publications
(39 reference statements)
2
49
0
Order By: Relevance
“…The object or recipient always receives the energy and responds in a useful way. This process is known as The Trivedi Effect ® -Biofield Energy Healing Treatment [21]. Biofield (Putative Energy Field) based Energy Therapies are used worldwide to promote health and healing.…”
Section: Introductionmentioning
confidence: 99%
“…The object or recipient always receives the energy and responds in a useful way. This process is known as The Trivedi Effect ® -Biofield Energy Healing Treatment [21]. Biofield (Putative Energy Field) based Energy Therapies are used worldwide to promote health and healing.…”
Section: Introductionmentioning
confidence: 99%
“…Most of Nocardial infections occur in the United States due to inhalation of airborne spores or mycelial fragments from the environmental sources [6]. The most common manifestation of Nocardial disease is pulmonary nocardiosis [7], extrapulmonary disease [8], and ocular Ampere's law, which states that the moving charge produces magnetic fields in the surrounding space [15,16]. Thus, a human body emits the electromagnetic waves in the form of bio-photons that is also known as ultra-weak photon emissions (UPE).…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, the Harold Saton Burr, had performed the detailed studies on the correlation of electric current with physiological process and concluded that every single process in the human body had an electrical significance. Recently, it was discovered that all the electrical process happening in body have strong relationship with magnetic field as required by Ampere's law, which states that the moving charge produces magnetic fields in surrounding space [5,6]. Thus, the human body emits the electromagnetic waves in form of bio-photons, which surrounds the body and it is commonly known as biofield.…”
Section: Introductionmentioning
confidence: 99%